Filtering and Wavelet Transform Algorithm for Old Document Image Restoration - Samosir, Ridha Sefina (Bina Nusantara University, 2017)
The aim of this research was to develop image restoration system using filtering and wavelet transform algorithm. Data collection was through observation and system was developed using prototyping model. Result of this research is a computer based on system to restore image containing noise. Based on the research process, filtering and wavelet transform algorithm can used to restore old document image from interferences (noise).